Manajemen Integrasi Kurikulum Berbasis Nilai Islam dalam Pembentukan Kemapuan Akademik dan Keterampilan Santri SMK di Pesantren Komarul Huda Bagu - Awza Fhatarani Aulia; Muhammad; Edi Muhammad Jayadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the implementation of an integrated curriculum between the national curriculum and the pesantren curriculum in vocational high schools (SMK) based on Islamic boarding schools through a literature review approach. This study is important considering the need for an educational model that can balance vocational competencies with the development of religious character in the context of modern workforce demands. The method used is a literature review by examining various scientific journals and relevant research findings related to curriculum integration and character education. Data were collected through documentation study and analyzed using descriptive analysis with a synthesis approach to compare and interpret previous research findings. The results indicate that the implementation of an integrated curriculum has a positive impact on improving students’ competencies and character development. Students tend to demonstrate better academic abilities, enhanced vocational skills, and strong religious values through the integration of learning processes, supported by a boarding school system that emphasizes discipline, worship practices, and social interaction. However, several challenges such as high academic workload, scheduling conflicts, and limited teacher competence still affect the effectiveness of implementation. Therefore, integrated curriculum implementation is an important strategy in improving the quality of education, but it requires comprehensive management, collaboration, and continuous development to achieve optimal outcomes.